Before and during the pandemic: teaching practices and teacher training in different school levels and grades - Di Blas, Nicoletta; Fabbri , Manuela; Ferrari , Luca; Trentini , Marco (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2021)
How did the teaching practices of teachers change during the Covid-19 emergency? How did the teachers train to deal with it? The case study presented in this article is based on data collected through an online questionnaire administered to a sample of almost 1000 teachers (from kindergarten to upper secondary school) participating in a MOOC (“massive” online course) made available by HOC-LAB of the Politecnico di Milano between March and June 2020. The results tell us that remote teaching is significantly adopted when the pandemic arrives, with an increase in the synchronous mode compared to the asynchronous one as the school level increases. New forms of interaction between teacher and pupils are born (individual meetings, small group meetings in extra-school hours); there is a correlation between the commitment to guarantee synchronous lessons and the availability for these further meetings (proactive approach), as well as between the sharing of videos (found on the internet) and the sharing of asynchronous materials compared to synchronous meetings (more “traditional” approach). As for training, teachers have resorted to forms that are not particularly institutionalized (MOOCs, web resources, colleagues...), confirming an already existing pre-pandemic trend.